2015
DOI: 10.1002/hyp.10582
|View full text |Cite
|
Sign up to set email alerts
|

New mapping techniques to estimate the preferential loss of small wetlands on prairie landscapes

Abstract: Abstract:Reliable estimates of wetland loss require improved wetland inventories and effective monitoring programmes. The Prairie Pothole Region of North America is experiencing rapid urban, agricultural and economic development, which places wetlands at risk, especially small geographically isolated wetlands. This loss is concomitant with a loss of ecosystem services. To improve upon current wetland inventories, a method for mapping wetlands using an automated object-based approach was developed for a regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…() noted that consolidation drainage in the PPR results in landscape changes from many, smaller wetlands to fewer, larger wetlands. Van Meter and Basu (), Serran and Creed (), and Serran et al. () found that smaller wetlands have been disproportionately lost across the Prairie Pothole landscape.…”
Section: Hydrological Physical and Chemical Functions Of Nfwsmentioning
confidence: 99%
“…() noted that consolidation drainage in the PPR results in landscape changes from many, smaller wetlands to fewer, larger wetlands. Van Meter and Basu (), Serran and Creed (), and Serran et al. () found that smaller wetlands have been disproportionately lost across the Prairie Pothole landscape.…”
Section: Hydrological Physical and Chemical Functions Of Nfwsmentioning
confidence: 99%
“…For the classification, different scenarios were implemented aiming at assessing the added value of the different derivatives generated in the previous processing steps. All scenarios included NDVI, NDWI and elevation, as their contribution is considered to be effective in recent studies [52][53][54]. Initially (SB), only the original S2 channels were used.…”
Section: Post-classification Correctionsmentioning
confidence: 99%
“…; Cheng and Basu ), and biological (e.g., Fairbairn and Dinsmore ; Zamberletti et al. ) services; yet, these systems are being lost at increasing rates (VanMeter and Basu ; Serran and Creed ; Sofaer et al. ; Jones et al.…”
Section: Characterizing Hydrologic Connectivity Of Non‐floodplain Wetmentioning
confidence: 99%